Pembuatan Bunga Hias dan Tempat Pensil untuk Mengurangi Sampah Plastik di Sekitar Kita - Reanita Anggis Deraya; Iva Anissya Putri; Anggi Arum Sri Lestari (PT.Mantaya Idea Batara, 2022)
Everyday life, humans will not be separated from basic needs, the rest will be disposed of as garbage. Garbage is a serious concern for the people of Indonesia. Especially the stalls that sell various sachets of drinks or sachets of food and wrap them in plastic bags. Some people are still confused about how to reduce the plastic waste. Lack of public understanding of the bad impact of waste, especially plastic waste, will have a significant impact on people's lives and health. In addition, plastic waste cannot be eradicated even if it is burned, and it takes millions to tens of millions of years for plastic waste to decompose in the soil. This negative influence must be turned into a positive one and utilized for the benefit of society. Processing plastic waste is a task that can be done by anyone and can produce financial results. Plastic waste must be recycled into products with high economic value. Therefore, a solution was made to reduce the negative impact of plastic waste, namely by creating decorative flowers and pencil cases. This is expected to reduce or even eliminate the negative impact of the accumulated plastic use.